An investigation into the impact of a mindfulness-based intervention on the anxiety of primary-aged children diagnosed with Autism Spectrum Disorder - Summers, Kirstie (2020)
There is growing recognition of the role schools can, and should have, in supporting children and young people’s mental health (Department of Health (DoH) & Department of Education (DfE), 2017). Evidence suggests potential benefits of utilising mindfulness-based interventions with children in primary schools to reduce anxiety (e.g. van de Weijer-Bergsma et al., 2014). However, there is a noticeable lack of research investigating the application of mindfulness-based interventions within children diagnosed with Autism Spectrum Disorder (ASD), who appear particularly vulnerable to experiencing anxiety (van Steensel et al., 2011). Accordingly, this study presents an investigation into the impact of a teacher delivered mindfulness-based intervention on the anxiety of children diagnosed with ASD.